Fungal pneumonia mimicking lung cancer - Chengtao Feng; Zhihong Zhao; Sheng Zhao; Zhiyong Deng; Long Chen (IDCases)
A 55-year-old woman with uncontrolled diabetes presented with a persistent cough and low-grade fever for one month. Initial investigations revealed leukocytosis, elevated CRP, and a 6.1 cm × 5.8 cm mass in the left lung with features suggestive of malignancy on CT and PET/CT scans. However, bronchoscopy and histopathology confirmed a pulmonary fungal infection. The patient was treated with antifungal therapy, showing a favorable response with resolution of symptoms and reduction of the mass size. This case highlights the diagnostic challenges in distinguishing pulmonary fungal infections from malignancies, especially in immunocompromised patients with diabetes. The presence of diabetes contributed to the patient’s susceptibility to fungal infections, which mimicked lung cancer on imaging. The importance of maintaining a broad differential diagnosis, including fungal infections, in patients with risk factors and atypical imaging findings is emphasized. Early suspicion and appropriate antifungal therapy are crucial to avoid misdiagnosis and improve outcomes.